Managing International Students in Chinese Universities: A Review of Policies, Practices, and Challenges - Nuruddin Ahmed Masud; MST Taherun Nesa Subarna; San Su Su San; Ki Bong Kim (Goodwood Publishing, 2026)
Purpose: This study systematically reviews the existing research on the management of international students in Chinese Universities and examines national policy frameworks, institutional practices, and implementation challenges within the broader context of higher education internationalization. Methodology: A PRISMA-guided systematic review was conducted on English-language, peer-reviewed articles and policy documents published between 2013 and 2026. The selected studies were analyzed using thematic synthesis to identify recurring patterns across policy, institutional, and student experience dimensions. Results: The findings indicate that China has developed a comprehensive regulatory framework governing admissions, visas, scholarships, and quality assurance. However, institutional implementation varies substantially, resulting in uneven student experiences. Key challenges include language barriers, inconsistent academic standards, limited administrative coordination, and difficulties with cultural integration. A recurring misalignment between policy intentions and institutional capacity was identified. Conclusions: Overall, effective international student management depends on a stronger alignment between national policy and institutional capacity. Limitations: As a literature-based review is limited to English-language sources, the findings may not fully capture Chinese-language scholarships or recent unpublished policy developments. Contributions: This study advances the field by proposing an integrated, results-based framework that explains how policy–practice alignment shapes international student outcomes in Chinese higher education. The review offers actionable insights for policymakers and university leaders seeking to enhance governance coherence and institutional capacity at emerging global education destinations.